Relationship Between Personality Traits and Nursing Professionalism - Behnam Masmouei; Hossein Bazvand; Mehdi Harorani; Mohammad-Rafi Bazrafshan; Zahra Karami; Mozhgan Jokar (Iran University of Medical Sciences, 2020)
Background: Professionalism is among the major concepts of nursing. Besides, nursing professionalism is often associated with attitudes, knowledge, and behaviors that underlie the successful clinical practice. Personality traits can affect various aspects of an individual's life. Accordingly, the present study aimed to determine the relationship between personality traits and nursing professionalism.  Methods: A cross-sectional correlational study was conducted on 205 nurses in teaching hospitals of Khoramabad City, Iran, in 2017. The study subjects were recruited by the stratified sampling method. NEO Personality Inventory and Goze Professional Behavior questionnaire were used to collect the required information. Then, the obtained data were analyzed by SPSS using descriptive and inferential statistics.  Results: Nursing professionalism had a direct relationship with extraversion (r=0.330, P<0.05), conscientiousness (r=0.333, P<0.05), and agreeableness (r=0.172, P=0.014); it also had an inversed relationship with neuroticism (r=- 0.161, P=0.021).  Conclusion: The Big Five personality traits are strongly related to nursing professionalism; with conscientiousness and extraversion as the most pronounced traits. Nurses' attitudes are partly rooted in their personality traits and these attitudes affect the nurse-patient relationship. Therefore, it is suggested that these characteristics be considered in appointing nurses in different departments.